Coal Gasification Technology to Support the Energy Transition: Opportunities and Challenges - Dita Aprilia Istiqamah; M. Sidik Boedoyo; Suyono Thamrin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia is a country that has quite abundant coal reserves. Coal reserves are most widely spread in Kalimantan and Sumatra and several other areas. When the production of other fossil energy such as petroleum decreases, the use of coal energy sources actually increases. However, coal is also known as a dirty fossil fuel because its use has a negative impact on the environment. This needs to be paid attention to in order to develop innovations in using coal that are more environmentally friendly, so that they can also support the energy transition to achieve the Net Zero Emission (NZE) target. The energy transition is a process that must be carried out by countries in the world to reduce carbon emissions which can cause climate change and global warming. The agreement on the energy transition aims to increase the use of clean energy. The energy transition does not have to eliminate coal. However, coal requires innovation for more environmentally friendly use. One of the environmentally friendly coal utilization technologies is coal gasification. In the road map for the development and utilization of coal by applying environmentally friendly technology through coal gasification, one of which is the coal development program to produce methanol and DME.